Road safety, accident problems and ways to improve safety - Stepanov I. V., Nikishkin A. V., Stepanovskikh V. V. (Topical issues of law, economic and management, 2020)
The article discusses the factors that contribute to the Commission of road accidents, as well as ways to ensure the safety of road users. Road traffic accident prevention becomes one of them the most serious socio-economic problems of the modern world. The results of the Federal target program on the dynamics of the level of road traffic accidents are presented.
Keywords: безопасность дорожного движения; road safety; причины дорожно-транспортных происшествий; нарушение правил дорожного движения; социальная напряженность; агрессивная культура вождения; обеспечение безопасности дорожного движения; программы государства; causes of road accidents; violation of traffic rules; social tension; aggressive driving culture; state programs